Analyzing relationship between ERP utilization and lean manufacturing maturity of Turkish SMEs. Issue 3 (8th April 2014) - Iris, Cagatay; Cebeci, Ufuk
Abstract : Purpose: – The purpose of this paper is to understand how effective Turkish small and medium size enterprises (SMEs) use enterprise resource planning (ERP) systems in module aspect and to assess the adherence to lean manufacturing requirements. Obtaining each efficiency result separately is not adequate to make an inference about relationship between ERP and lean practices. Hence, a relational model is developed to analyze correlation between use of ERP and lean manufacturing implementation in white goods manufacturing SMEs of Istanbul, Turkey. Design/methodology/approach: – The examination of the proposed conceptual framework is made by statistical analyses. In parallel, leveling efficiency of each enterprise requires an expert analysis in order to obtain a fair comparison. Hence, authors have visited each facility to evaluate performance of ERP efficiency and lean manufacturing applications. In Istanbul region, 53 of total listed SMEs are visited. The questionnaire survey is designed by considering different scales of performance. Exploratory factor analyses and various correlation analyses are applied to figure out relationship between ERP use and lean manufacturing. Findings: – Interaction with rapid development of information technology (IT) and progress in modern production management strategies have emerged. Obtained results show that Turkish SMEs have widely initiated lean production practices. However, applications are in initial level in the most cases. In respect to ERP systems, enterprises are more active, some basic modules are extensively used. Another finding of this study implies that effective usage of specific ERP modules can contribute toward applying lean principles, vice versa. Research limitations/implications: – The whole sample space of white goods SMEs could not be covered due to the fact that, each facility is visited and field studies are done. However, sample size calculations prove that attained feedback is statistically significant (adequate) to reflect sample space. Originality/value: – The literature studies reveal that there is an obvious lack of studies which focus on relationship between ERP use and lean manufacturing. Finding such a correlation helps IT-practitioners to design ERP modules by assessing related requirements of lean philosophy.